2015
DOI: 10.1071/wf14219
|View full text |Cite
|
Sign up to set email alerts
|

Sierra Nevada fire severity conclusions are robust to further analysis: a reply to Safford et al.

Abstract: Safford et al. (this issue) question our finding in IJWF, inHanson and Odion (2014) ('H&O'), that fire severity has not increased in Sierra Nevada forests. Safford et al. ('SMC') suggest that our inclusion of national park and private lands, prescribed burns and forest types with relatively infrequent fire regimes (e.g. lodgepole pine (Pinus contorta) and red fir (Abies magnifica)) could potentially have influenced our findings, and that restricting the analysis to US Forest Service lands, and forest types wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Examining trends from 1984 to 2006 for large ecoregions in the north-and southwest USA, Dillon et al [71] found no significant increase in the proportion of annual area burned at high severity for five of the six regions considered, with the southern Rockies being the exception. For the Sierra Nevada region (California), which was not covered in the previous study [71], Hanson & Odion [72,73] found no general increase in fire severity within the period 1984-2010. Considering ten national forests in California for the same period, Miller & Safford [74] found a significant increase in burn severity for yellow pine -mixed conifer forests.…”
Section: Have Fire Impacts Increased In Many Regionsmentioning
confidence: 92%
“…Examining trends from 1984 to 2006 for large ecoregions in the north-and southwest USA, Dillon et al [71] found no significant increase in the proportion of annual area burned at high severity for five of the six regions considered, with the southern Rockies being the exception. For the Sierra Nevada region (California), which was not covered in the previous study [71], Hanson & Odion [72,73] found no general increase in fire severity within the period 1984-2010. Considering ten national forests in California for the same period, Miller & Safford [74] found a significant increase in burn severity for yellow pine -mixed conifer forests.…”
Section: Have Fire Impacts Increased In Many Regionsmentioning
confidence: 92%
“…A better understanding of avian responses to fire can help inform the debate surrounding the natural range of variability of the fire regime and guide forest management approaches in fire‐maintained systems. In dry forests of western North America, there is an ongoing debate regarding historical fire regimes (Williams and Baker , Hanson and Odion , Miller and Safford ), which often serve as restoration targets (Varner et al. , Millar et al.…”
Section: Introductionmentioning
confidence: 99%
“…While there are some equivocal indications of increases in fire severity (e.g., increases in the area of high-severity fire, but not the proportion of high-severity fire effects) in some regions, such as portions of the southwestern United States and the southern Rockies (Dillon et al, 2011), most studies have found no increase in fire severity in most forested regions of the western United States Collins et al, 2009;Dillon et al, 2011;Hanson and Odion, 2014). One recent study reported an increase in fire severity in the Sierra Nevada , whereas a larger analysis found no such trend Hanson and Odion, 2015). Thus, whether the gaps between current and historical fire occurrence are closing in these regions is unclear, suggesting that actions to allow or facilitate more managed wildland fire (fires caused by lightning that are allowed to burn for ecological benefit) should be encouraged where ongoing fire deficits exist and fires can burn under safe conditions.…”
Section: Are Megafires Increasing?mentioning
confidence: 89%